Identification of Two Immune Related Genes Correlated With Aberrant Methylations as Prognosis Signatures for Renal Clear Cell Carcinoma - Yao, Zhi-Yong; Xing, Chaoqung; Liu, Yuan-Wu; Xing, Xiao-Liang (Frontiers in Genetics, 2021)
Almost 75% of renal cancers are renal clear cell carcinomas (KIRC). Accumulative evidences indicated epigenetic dysregulations are closely related to the development of KIRC. Cancer immunotherapy is an effective treatment for cancers. The aim of this study was to identify immune-related differentially expressed genes (IR-DEGs) associated with aberrant methylations and construct a risk assessment model using these IR-DEGs to predict the prognosis of KIRC. Two IR-DEGs (SLC11A1 and TNFSF14) were identified by differential expression, correlation analysis and Cox regression analysis, and risk assessment models were established. Area under the receiver operating characteristic (ROC) curve (AUC) was 0.6907. In addition, we found that risk scores were significantly associated with 31 immune cells and factors. Our present study not only shows that 2 IR-DEGs can be used as prognosis signatures for KIRC, but also provides a strategy for the screening suitable prognosis signatures associated with aberrant methylation in other cancers.